Використання положень статті 206 Кримінального процесуального кодексу при здійсненні захисту у кримінальному провадженні - Гловюк Ірина Василівна; Гловюк Ирина Васильевна; Glovyuk Iryna V. (My University, 2016)
Стаття присвячена дослідженню проблем нормативної регламентації та практики реалізації загальних обов’язків судді щодо захисту прав людини у контексті реалізації функції захисту. На основі аналізу положень КПК, практики Європейського суду з прав людини, судової практики національних судів охарактеризовано особливості доказування при реалізації цієї групи повноважень слідчого судді, запропоновані зміни та доповнення до ст. 206 КПК.

Статья посвящена исследованию проблем нормативной регламентации и практики реализации общих обязанностей судьи по защите прав человека в контексте реализации функции защиты. На основе анализа положений УПК, практики Европейского суда по правам человека, судебной практики национальных судов охарактеризованы особенности доказывания при реализации этой группы полномочий следственного судьи, предложены изменения и дополнения в ст. 206 УПК.

The article is dedicated to the study some issues of legal regulation and practice of realization of general obligations of judge concerned to the protection of human rights during the implementation of function of defense. It was outlined that investigative judge should implement his authorities without reference to form of receiving information that composes reasonable suspicion that within the court’s territorial jurisdiction, there is a person who has been deprived of his liberty without valid court’s deci- sion, or has not been released from custody after the payment of bail. The capacity of examination of issue of legality and reasonableness of apprehension of person due to the suspicion in commitment a crime according to the art. 207–208 of CPC of Ukraine is outlined in art. 206 of CPC of Ukraine. It was proved that if person is apprehended illegally and unreasonably and term of apprehension was not ended, investigative judge will be obligated to check out the legality and reasonableness of apprehension exceeding the limits of examination of application. It was proved that local facts in proof in realization judge’s authorities according to the art. 206 CPC of Ukraine consist on such circumstances as: 1) deprivation of liberty; 2) legal ground for deprivation of liberty. The burden of proof related to the legal ground of deprivation of liberty lays upon investigator and prosecutor. If investigative judge refuses in immediate liberation of person, he should state the reasons and evidences that refute statements of defense concerned to illegal deprivation of liberty in details. The applicant is not obligated to lodge the evidences to prove the enforcement of violence towards him during the apprehension and custody in the competent public authority concerned, state institution (public authority, state institution empowered to keep in custody); for commission to provide forensic medical research of person and to study facts expounded in application the appropriate application of person is enough. Analyzing statements of CPC of Ukraine, practice of European court of Human rights and practice of national courts, the peculiarities of proving in implementation these authorities are outlined. The changes and additions for art. 206 of CPC of Ukraine were proposed.
Гловюк І. В. Використання положень статті 206 Кримінального процесуального кодексу при здійсненні захисту у кримінальному провадженні / І. В. Гловюк // Вісник кримінального судочинства. - 2016. - №2. – С. 24-30.
Keywords: захист; слідчий суддя; загальні обов’язки судді щодо захисту прав людини; доказування; розслідування жорстокого поводження; защита; следственный судья; общие обязанности судьи по защите прав человека; доказывание; расследование жестокого обращения; defense; investigative judge; general obligations of judge to protect human rights; proving; the investigation of abuse